Dinamika Psikologis Pelaku Kejahatan Pembunuhan Berencana di Lapas Klas 1 Surabaya - Lowis, Inez (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
Murder, whether planned or not, is not a serious crime. The high number of murder cases that continues to increase is of particular concern to every country, including Indonesia. Many factors influence individuals to commit crimes such as murder. This research was conducted to determine the psychological factors that influence the murder committed by murder convicts. The research was conducted using a qualitative design, using a case study phenomenology approach. The results and findings show that high aggression, impulsive tendencies, not having a good role model, and low emotional regulation skills are the main factors in the subject of committing murder. The intervention was carried out in the form of psychoeducation to the subject. The intervention was successful enough to find out about the factors that influence a crime and its causes and to help subjects understand how to regulate emotions properly.